2022
DOI: 10.3389/fsoc.2022.807591
|View full text |Cite
|
Sign up to set email alerts
|

A Change in Work-Family/Life or a Return to Traditional Normative Patterns in Spain? Systematic Review

Abstract: Family policies to reduce conflict in work-life balance and promote gender equality advanced significantly at the legislative level in Spain in the first decades of the twenty-first century. These advances include the 2007 Law for Equality between Men and Women and the extension of paternity leave to 16 weeks in 2020. However, advances in care work and at the professional level have been limited. The COVID-19 pandemic has intensified existing imbalances in family-work responsibilities in general and the ICT ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 59 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…The research found the interaction between culture and gender, with greater WIF and FIW, reported in countries with more traditional than egalitarian gender role beliefs [ 15 ]. The systematic review [ 16 ] suggests changing the expectations and practices around work-family balance due to current cultural changes in the technological revolution, job insecurity, family diversity, and new masculinities. Therefore, more research on work-family balance is required from a cross-cultural and gender comparative perspective.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The research found the interaction between culture and gender, with greater WIF and FIW, reported in countries with more traditional than egalitarian gender role beliefs [ 15 ]. The systematic review [ 16 ] suggests changing the expectations and practices around work-family balance due to current cultural changes in the technological revolution, job insecurity, family diversity, and new masculinities. Therefore, more research on work-family balance is required from a cross-cultural and gender comparative perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The imbalance between family and work responsibilities has increased during the COVID-19 pandemic, as suggested by a recent systematic review [ 16 ]. One of the most sensitive groups for high WFC and FWC was parents of minor children [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations